Identification and Functional Characterization of a Low-Density Lipoprotein Receptor Gene Pathogenic Variant in Familial Hypercholesterolemia - Shu, Hong-Yan; Zhang, Wei; Zheng, Cong-Cong; Gao, Man-Yun; Li, Yong-Cun; Wang, Yan-Gang (Frontiers in Genetics, 2021)
We report a single-point variant of low-density lipoprotein receptor (LDLR) in a Chinese proband with a clinical diagnosis of familial hypercholesterolemia (FH) with comprehensive functional analysis. Target exome capture-based next-generation sequencing was used for sequencing and identification genomic variants in the LDLR gene. The expression, cellular location and function of the mutant LDLR were analyzed. Sequencing of LDLR in FH patients indicated a point variant of a single base substitution (G